Estudo experimental do uso de rebolos convencionais na usinagem do aço VP-50 utilizado na retificação cilíndrica, por meio de diferentes métodos de lubri-refrigeração - Anjos, Marco Antônio dos [UNESP] (2015)
Grinding is an accurate machining process, one of the most expressive steps in the manufacture of molds for thermoplastic injection. The grinding wheel abrasive tool is reponsible for removal. The knowledge of their tehcnical characteristics, advantages, defects and working conditions are essential for product engineers, process and, of course, to the industrial area manangers, which identify the most appropriate wheel to perform the grinding process. Among the steels used in the manufacture of molds for thermoplastic injection highlight the VP-50 steel, which was the steel used in this experiment being machined by the cylindrical grinding process. In the grinding process was also adopted for the purpose of experiment two methods of lubrification and cooling them with the conventional method with plenty of lubrification and cooling, and the MQL is the technique with minimal amount of lubrification and cooling. The objetive of this study was to analyze comparatively cutting performance, performed with three types of conventional grinding wheels: grinding wheel white aluminum oxide, green silicon carbide grinding wheel and grinding of black silicon carbide with white aluminum oxide. Results were analyzed and compared by the output variables such as behavior of the tangential cutting force, surface roughness, acoustic emission, G ratio (volume of material removed/volume of material removed), optical microscopy (to check if there thermal damage), and micro hardness. Observing acceptable levels of roughness characteristic of the process, it was also observed that the grinding green silicon carbide had the best wear resitance in relation to the other wheels. The grinding wheel of black silicon carbide obtained the lowest range of values of circularity. After metallographic examination of the specimens was found that there was little formation of new alloying elements in the ground the ground surface, to confirm that a slight increase in...